Child and Adolescent Forensic Psychiatry Experiences During the COVID-19 Pandemic - Birsen Senturk Pilan; Ipek Inal Kaleli; Serpil Erermiş; Ahsen Kaya; Sezen Köse; Burcu Özbaran; Tezan Bildik (Galenos Publishing House, 2022)
Objective: Coronavirus disease-2019 (COVID-19) changed the status-quo in psychiatric interview with the advent of telemental health practices, save for a select group of patients; forensic psychiatric interviews among them. The present study aimed to identify the predictors of completing forensic psychiatric evaluations mandated by the judicial authorities in the hospital setting during the COVID-19 outbreak. Method: Twenty-six patients who had completed an initial forensic psychiatric assessment and were required to complete a child and adolescent forensic psychiatry board interview during the height of the COVID-19 pandemic were recruited. Their records were retrospectively examined, sociodemographic data, Beck Depression Inventory (BDI), the Screen For Child Anxiety Related Disorders (SCARED), and Wecshler Intelligence Scale for Childrenrevised scores were recorded and analyzed. Results: Statistical analysis revealed an association between conduct disorder and concomitant substance use with missed appointments, and maternal employment and completed interviews. BDI and SCARED total scores showed no difference between the patients who missed or completed their mandatory forensic psychiatry board assessment. BDI individual items of loss of pleasure (item 4), suicidality (item 9), and loss of interest (item 12) were associated with missed appointments. Conclusion: The results of this study support the established relationship between conduct problems and depressive symptoms, and this demographic group may be among the most affected by the limitation of access to mental health services during the COVID-19 pandemic, as they are already less likely to seek help overall.